The Impact of Mathematical Learning based on Sorogan Methods Assisted by Peer Tutors against Students' Mathematical-Concepts Understanding - Saputri, Dina; Budiman, Haris; Putra, Rizki Wahyu Yunian (Journal of Mathematical Pedagogy (JoMP), 2019)
This study aims to determine the effect of learning with Sorogan Methods on students' mathematical-concept understanding, knowing the effect of peer tutors on students' mathematical-concept understanding and find out the increase between sorogan methods assisted peer tutor and students' mathematical-concept understanding. The method used in this study was the Quasy Experiment method, this study used a one way variance analysis (ANAVA) technique with unequal cells. The results showed that there was an influence of the Sorogan Method on students' mathematical-concept understanding, where the Sorogan Method was better than the conventional learning model. There was an influence of the Peer Tutor Method on students 'understanding of mathematical concepts, where the Peer Tutor Method was better than the Conventional Learning Model. There was an increase in the Sorogan method of peer tutor assistance on students' mathematical-concept understanding. This study shows that the Peer Tutor Assisted Sorogan method has a good effect on students' mathematical-concept understanding.Keywords: the sorogan method, students mathematical-concept understanding, peer tutors.